Concentration of fetal plasma and amniotic fluid interleukin-1 in pregnancies complicated by preterm prelabour amniorrhexis. Issue 4 (April 1995) - Carroll, S G; Abbas, A; Ville, Y; Meher-Homji, N; Nicolaides, K H
Abstract : AIMS--To determine interleukin-1 beta (IL-1 beta) concentration in fetal and maternal plasma and amniotic fluid from pregnancies complicated by preterm prelabour amniorrhexis and to define the relation of this cytokine to intrauterine infection and the onset of labour. METHODS--Cross-sectional study of 23 pregnancies complicated by preterm prelabour amniorrhexis. Enzyme linked immunoassay was used to measure IL-1 beta concentration in fetal and maternal plasma and amniotic fluid. In each case, fetal blood and amniotic fluid were cultured for micro-organisms. RESULTS--In pregnancies with positive fetal blood and/or amniotic fluid cultures, plasma and amniotic fluid concentrations of IL-1 beta were higher and the interval between amniorrhexis and onset of labour was shorter than in the non-infected group. There were no significant associations between fetal plasma IL-1 beta and maternal plasma or amniotic fluid IL-1 beta concentrations, fetal leucocyte count or the interval between amniorrhexis and the onset of labour. CONCLUSIONS--These findings suggest that although intrauterine infection is associated with increased IL-1 beta concentrations in fetal plasma and amniotic fluid, there is no significant association between the concentration of IL-1 beta and the interval between amniorrhexis and the onset of labour.